Polymorphonuclear leukocytes (PMNs) use different, strain-dependent mechanisms to kill the parasite Trichomonas vaginalis - Frances Mercer; Sandip Kumar Mukherjee; Chi-Lee Ho; Katherine Muratore; Patricia J. Johnson (mBio)
ABSTRACT The unicellular parasite Trichomonas vaginalis (Tv) causes trichomoniasis, the most common non-viral sexually transmitted infection in humans. Trichomoniasis symptoms and sequelae vary substantially, and in vitro analyses have shown that strains differ extensively in their ability to infect and lyse cells of the urogenital tract. Polymorphonuclear leukocytes (PMNs) are known to kill Tv, yet to date, no studies have examined strain differences in PMN killing of this extracellular pathogen. Here, we have examined four strains of Tv for their susceptibility to killing by PMN trogocytosis, a process by which PMNs incrementally acquire fragments of the parasite’s plasma membrane leading to parasite death. Two strains were found to be rapidly and efficiently killed by trogocytosis, whereas the other two strains, although subjected to PMN trogocytosis, were resistant to killing. Strains that resist trogocytic killing were found to have an enhanced plasma membrane resealing capacity. Furthermore, these trogocytosis-resistant strains were susceptible to a later-stage killing mechanism that is significantly reduced in the presence of DNase, consistent with killing by neutrophil extracellular traps (NETosis). Together, our data reveal the use of multiple mechanisms for PMN killing of Tv and demonstrate strain-dependent resistance to rapid killing by trogocytosis, driven by membrane repair. Trogocytosis-resistant strains are subsequently killed by NETosis, likely circumventing the replacement of trogocytosis-sensitive strains by resistant strains over evolutionary time. Together, our data demonstrate that PMNs use different modalities to kill Tv and that Tv strains differ in their PMN-evasive properties.IMPORTANCETrichomonas vaginalis (Tv) causes the third most prevalent sexually transmitted infection globally and is the most common cause of vaginitis in the United States. Despite its prevalence, little is known about how the human immune system combats and kills Tv. We have previously shown that the abundant white blood cells called polymorphonuclear leukocytes (PMNs), known to kill pathogens using multiple mechanisms, kill Tv using a rapid-killing mechanism called trogocytosis. Here, we examined whether Tv clinical isolates with different pathogenic properties are killed by PMNs using other mechanisms. We demonstrate that clinical isolates that are resistant to trogocytic killing are better at plasma membrane repair and are efficiently killed by a late-stage mechanism called NETosis. Thus, PMN uses multiple, strain-specific mechanisms to kill Tv isolates with varying virulence properties. This study sheds light on host cell killing mechanisms that may impact pathogenic outcomes and sequelae during Tv infection.